Pokdarwis Gubugklakah : Menggapai Asa melalui Sadar Wisata - Theo Andrianto; Marchellino Fergie Sanjaya; Ryan Dharmawan; Budi Setiawan (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
Pokdarwis (Tourism Awareness Group) Gubugklakah acts as the main driver in educating and empowering village communities in Gubugklakah, Poncokusumo District, Malang Regency. The purpose of this research is to identify the role of Pokdarwis Gubugklakah in developing local community-based tourism. The research method in this paper is a qualitative approach by interviewing the head of Pokdarwis Gubugklakah, conducting direct field observations and using several literature reviews. Pokdarwis Gubugklakah was established in 2010 by 20 members, chaired by Mr. Anshori, Pokdarwis Gubugklakah has become a group that brings reforms that bring success, especially in terms of tourism in Gubugklakah village. The success of Gubugklakah Tourism Village can be seen from the achievements that have been recognized by the state. Pokdarwis Gubugklakah emphasizes the importance of the concept of Tourism Awareness which consists of two aspects, namely being a good host and a wise guest.